ҚАРАҚАЛПАҚ ХАЛЫҚ ҚОСЫҚЛАРЫНЫҢ СЮЖЕТЛИК ӨЗГЕШЕЛИГИ - Баўатдинова, С. (FAN va JAMIYAT, 2019)
The article considers the nature of Karakalpak folk songs. It is determined that every genre of folk songs has a history. They have their own program, which was formed for the centuries, with poetic, compositional features. The main characteristic feature of the songs of the Karakalpak people at the present time is the lack of variation.